Ninja hacking : unconventional penetration testing tactics and techniques - Wilhelm, Thomas (Syngress/Elsevier, 2011)
Ever thought of using the time-tested tactics and techniques of the ancient ninja to understand the mind of today's ninja, the hacker? As a penetration tester or security consultant you no doubt perform tests both externally and internally for your clients that include both physical and technical tests. Throw traditional pen testing methods out the window for now and see how thinking and acting like a ninja can actually grant you quicker and more complete access to a company's assets. Get in before the hacker does with these unorthodox techniques. Use all of the tools that the ninja.